ANALISIS NILAI KEADILAN PADA SYARAT PENAHANAN TERSANGKA DALAM PENYIDIKAN (PERBANDINGAN KUHAP 1981 DAN KUHAP 2025) - Nisa Amalina Adlina (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
This study was conducted with two primary objectives. First, it examines the concept of justice in relation to the benchmark of investigators’ concerns used to assess and determine the detention of suspects under the subjective detention requirement stipulated in Article 21 paragraph (1) of the Indonesian Criminal Procedure Code (KUHAP) of 1981. Second, it analyzes a comparative assessment of the value of justice embodied in the detention requirements for suspects under Article 21 paragraph (1) of the 1981 KUHAP and Article 93 paragraph (5) of the 2025 KUHAP. This research employs normative legal research, positioning law within a system of norms by referring to statutory regulations relevant to the subject matter. Data were collected through library research and analyzed using a descriptive-analytical approach by systematically presenting the issues and examining them in depth. The findings indicate that the value of justice inherent in the subjective detention requirement under Article 21 paragraph (1) of the 1981 KUHAP—specifically regarding circumstances that give rise to “concerns” that a suspect may abscond, destroy or remove evidence, and/or reoffend—is not aligned with the principle of equality before the law. In practice, this provision relies solely on the subjective assessment of the authorized investigator, thereby creating room for discriminatory treatment in determining whether suspects should be detained. The reform of the KUHAP through Law No. 20 of 2025 reflects an effort to enhance the value of justice by formulating more objective detention requirements under Article 93 paragraph (5) compared to Article 21 paragraph (1) of the 1981 KUHAP. Nevertheless, the reformed detention provisions still lack clear evaluative benchmarks and implementing regulations, which continues to allow investigative discretion in determining whether a suspect may be detained. Consequently, the value of justice has not yet been fully guaranteed.